Associations between resting state brain activity and A1 adenosine receptor availability in the healthy brain: Effects of acute sleep deprivation - Li, Changhong; Kroll, Tina; Matusch, Andreas; Aeschbach, Daniel; Bauer, Andreas; Elmenhorst, Eva-Maria; Elmenhorst, David (Frontiers in Neuroscience, 2023)
Introduction Previous resting-state fMRI (Rs-fMRI) and positron emission tomography (PET) studies have shown that sleep deprivation (SD) affects both spontaneous brain activity and A1 adenosine receptor (A1AR) availability. Nevertheless, the hypothesis that the neuromodulatory adenosinergic system acts as regulator of the individual neuronal activity remains unexplored. Methods Therefore, fourteen young men underwent Rs-fMRI, A1AR PET scans, and neuropsychological tests after 52 h of SD and after 14 h of recovery sleep. Results Our findings suggested higher oscillations or regional homogeneity in multiple temporal and visual cortices, whereas decreased oscillations in cerebellum after sleep loss. At the same time, we found that connectivity strengths increased in sensorimotor areas and decreased in subcortical areas and cerebellum. Discussion Moreover, negative correlations between A1AR availability and rs-fMRI metrics of BOLD activity in the left superior/middle temporal gyrus and left postcentral gyrus of the human brain provide new insights into the molecular basis of neuronal responses induced by high homeostatic sleep pressure.